Variation in grain yield, fodder quality and animal intake in two dual purpose legume crops: Mungbean and vegetable soybean grown in semi-arid tropical India - Nair, R.M.; Giri, R.R.; Boddepalli, V.N.; Prasad, Kodukula V.S.V.; Devulapalli, R.; Blümmel, Michael (Agricultural Research Communication Center, 2021)
Twenty six lines each of two legume crop species: mungbean [Vigna radiata (L.) R. Wilczek] and vegetable soybean [(Glycine max (L.) Merr.)] were evaluated for grain yield and fodder traits during 2013 in Hyderabad, India. Mungbean line, ML 818 was the best for nitrogen content and was also among the better performers for in vitro organic matter digestibility (IVOMD). Vegetable soybean line, Swarna Vasundhra registered high values for nitrogen content, haulm yield, pod yield and seed yield, while GC 84501-32-1 recorded high value for nitrogen content. In-vivo parameters such as dry (DMI) and organic matter intake (OMI), dry (DMD) and organic matter digestibility (OMD) and nitrogen (N) balance were determined after feeding sheep with haulms from selected lines of mungbean and vegetable soybean as supplements to a sorghum stover based ration. Vegetable soybean line, Swarna Vasundhra recorded the highest OMD while the mungbean line, VC 6510-151-1 recorded the highest nitrogen balance.